(3JMOjO GdGSJQGJjLjI GdGSJKeGQjI GdeKdj dTQcGJ JCejfGJ GdMjGI aj EWGQ JWHjb fXGe JNWjW ehGQO GdefTCI (B(ERP) (3heYGjjQ GdedGAI GdeGdjI (B/ s - (3EjeGf LeGd eMeO CMeO,s; (3GdSHGYj eMeO GdSHGYj Gdabjs (2023)
(3gOaJ GdOQGSI Edj JMOjO GdGSJQGJjLjI GdGSJKeGQjI GdeKdi dTQcGJ JCejfGJ GdMjGI aj EWGQ JWHjb fXGe JNWjW ehGQO GdefTCI (B(ERP) (3heYGjjQ GdedGAI GdeGdjI (BII, (3hPdc Yf WQjb bjGS GdYdGbI Hjf JWHjb eJWdHGJ eYGjjQ GdedGAI GdeGdjI (BII (3aj VhA eNGWQ GdShb hJMOjO GdfSH GdGSJKeGQjI GdeKdj aj VhA Jdc GdeNGWQ hCjVkG eYQaI JCKjQ JWHjb fXGe JNWjW ehGQO GdefTCI (B(ERP) (3Ydi GdCOGA GdGSJKeGQj HTQcGJ GdJCejf(B, (3hbO GYJeOJ GdOQGSI Ydi YjfI ef TQcGJ GdJCejf GdeUQjI hgi (B((3eUQ dJCejfGJ GdMjGI(B, (3GdegfOS dJCejfGJ GdMjGI(B, (3CdjGfR dJCejfGJ GdMjGI(B) (3hPdc NdGd GdaJQI (B(2010-2020) (3hbO Je GSJNOGe YOI CSGdjH EMUGFjI dbjGS hGNJHGQ GdYdGbI Hjf eJZjQGJ GdOQGSI eKd CSGdjH GdEMUGA GdhUaj cGdeJhSW hGdGfMQGa GdeYjGQj heUahaI GdGQJHGW hGdJHGjf hZjQge ef GdCSGdjH hGdeYGOdGJ GdQjGVjI GdJj SGYOJ GdHGMKI aj JMbjb gOa GdOQGSI(B, (3hJe GSJNOGe eLehYI ef GdHQGeL (BR(3, (BMATLAB , Python (3dGSJNQGL GdfJGFL GdEMUGFjI(B. (3hbO ChVMJ fJGFL GdJMdjd GdEMUGFj dJMOjO GdeMaXI GdeKdj ddTQcGJ ehVhY GdOQGSI aj EWGQ JWHjb fXGe GdedGAI GdeGdjI (BII (3aj VhA eNGWQ GdShb hcGfJ ceG jdj HGdfSHI dTQcI eUQ Cf CYdj fSHI ef GdYhGFO GdGSJKeGQjI GdJj JMbb CYdj YGFO eecf aj Xd GdeNGWQ GdJj JhGLg GdTQcI gj GdYGFO ef GdChQGb GdMchejI MjK HdZJ fSHJgG (B42% (3jdjgG GdYGFO ef GdCSge HfSHI (B29% (3jdjg GdYGFO ef GdfbOjI HfSHI (B20% (3jdjg GdYGFO ef GdSfOGJ (B7% (3Ke jdjg GdYGFO ef GdYbGQGJ (B1% (3Ke jdjg GdYGFO ef GdbQhV HfSHI (B1% (3YfO eSJhj eNGWQ (B12.5% . (3GdfSHI dTQcI GdegfOS Cf CYdj fSHI ef GdYhGFO GdGSJKeGQjI GdJj JMbbgG GdTQcI gj GdYGFO ef GdSfOGJ MjK HdZJ fSHJgG (B89% (3jdjg GdYGFO ef GdfbOjI HfSHI (B5% (3jdjg GdYGFO ef GdCSge HfSHI (B4%(3, hJTgO Cbd fSHI ef GdYhGFO GdGSJKeGQjI dTQcI GdegfOS hgj GdYGFO ef GdYbGQGJ MjK dG JMbb Cj YGFO Ydj GdCWdGb HjfeG jHdZ GdYGFO ef GdChQGb GdMchejI hGdYGFO ef GdbQhV fSHI (B1% (3dcd efgeG YfO eSJhj eNGWQ (B30%.s
(3CWQhMI (B((3OcJhGQg(B)-(3LGeYI GdbGgQI, (B2022.s
(3HHdjhLQGajG(B: (3U(B. 107-118.s
Keywords: (3GdJCejf Ydi GdMjGIs; (3eNGWQ GdShbs